Women in interventional cardiology: Update in percutaneous coronary intervention practice patterns and outcomes of female operators from the National Cardiovascular Data Registry®. Issue 4 (10th August 2015) - Wang, Tracy Y.; Grines, Cindy; Ortega, Rebecca; Dai, David; Jacobs, Alice K.; Skelding, Kimberly A.; Mauri, Laura; Mehran, Roxana
Abstract : Objectives: To examine the practice patterns and outcomes of percutaneous coronary intervention (PCI) procedures performed by female interventional cardiologists in the United States (U.S.). Background: Little is known about the prevalence, volume, case mix, and outcomes of PCI procedures performed by female interventional cardiologists. Methods: Using data from the National Cardiovascular Data Registry ®, we performed a retrospective study of 2, 465, 685 PCI procedures performed at 1, 431 U.S. hospitals between July 1, 2009 and June 30, 2013. Interventionalist sex was ascertained from the National Provider Identifier number of each operator. Results: Women accounted for only 4% (412/9, 179) of interventional cardiologists in the U.S., and performed 3% ( n  = 70, 009) of all PCI procedures during the time period studied. Forty‐one percent of female interventionalists operated at an institution with no other female operators. Female interventionalists performed a median of 48 PCI procedures per year (interquartile range: 22–87). Of the cases performed by female interventionalists, 77% were performed on patients with acute coronary syndrome, 3% on patients with cardiogenic shock, and 16% on call. In‐hospital mortality was low (1.8%), and was not significantly different between female operators with high (≥50 cases/year) versus low (1.95% vs. 1.75%, unadjusted P  = 0.12, adjusted OR: 1.03, 95% CI: 0.84–1.27) annual procedure volume. Conclusions: Female interventional cardiologists remain uncommon in contemporary U.S. practice. Performing only a very small proportion of PCI cases, female interventionalists are often low‐volume operators, yet no significant differences in patient mortality were observed in low‐ versus high‐volume operators. © 2015 Wiley Periodicals, Inc.